Factorial structure of aerobics athletes' fitness - T.V. Shepelenko; Zh.L. Kozina; M. Cieslicka; K. Prusik; R. Muszkieta; I.N. Sobko; O.A. Ryepko; T.A. Bazilyuk; S.B. Polishchuk; A.V. Osiptsov; V.M. Kostiukevych (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
The purpose of the research is to develop an algorithm of teams' formation in sport aerobics and to define factorial structure of athletes' fitness. Material : in the research sport aerobics' athletes (n=19) participated. All athletes are members of Kharkiv national team (Ukraine). All athletes underwent complete medical examination. The functional condition of an organism (arterial blood pressure, indicators of a variability of the rhythm of the heart, treadbahn testing), psycho-physiological state (time's determination of simple and complex reaction) were defined. The physical development and physical fitness and stability of vestibular system were also defined. The factorial and cluster analysis were used. Results : The algorithm of teams' formation in sport aerobics is developed for performances in various competitive categories. The algorithm contains all stages of standard procedure of the factorial and cluster analysis. In the factorial analysis the individual factorial values were also defined. Conclusions : The obtained data are recommended to be used at teams' formation for performances in various competitive categories: team formation for pair and group performances. The general and individual factorial structure of athletes' complex fitness is defined. It is possible to select athletes with similar qualities and with different qualities for the mixed performances. The determination of individual factorial structure of fitness permits to estimate objectively variants of athletes' formation in groups.